José Carlos Ruiz, El arte de pensar. Cómo los grandes filósofos pueden estimular nuestro pensamiento crítico, Almuzara 2022, s. 288. - Jeszka, Adam (Studia Gdańskie, 2023)
José Carlos Ruiz, El arte de pensar. Cómo los grandes filósofos pueden estimular nuestro pensamiento crítico, Almuzara 2022, s. 288.